2004
DOI: 10.1007/s10209-003-0069-3
|View full text |Cite
|
Sign up to set email alerts
|

The use of guidelines to automatically verify Web accessibility

Abstract: Accessibility is one of the key challenges that the Internet must currently face to guarantee universal inclusion. Accessible Web design requires knowledge and experience from the designer, who can be assisted by the use of broadly accepted guidelines. Nevertheless, guideline application may not be obvious, and many designers may lack experience to use them. The difficulty increases because, as the research on accessibility is progressing, existing sets of guidelines are updated and new sets are proposed by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 7 publications
0
50
0
2
Order By: Relevance
“…Most of them use automated accessibility testing tools in order to profile the community to gain an understanding of common accessibility problem areas (Abascal, Arrue, Fajardo, Garay, & Tomás, 2004). However, some studies found that a great percentage of them failed in the automated checking, so a manual analysis of the accessibility may find worse results (Curran, Walters, & Robinson, 2007).…”
Section: Related Workmentioning
confidence: 99%
“…Most of them use automated accessibility testing tools in order to profile the community to gain an understanding of common accessibility problem areas (Abascal, Arrue, Fajardo, Garay, & Tomás, 2004). However, some studies found that a great percentage of them failed in the automated checking, so a manual analysis of the accessibility may find worse results (Curran, Walters, & Robinson, 2007).…”
Section: Related Workmentioning
confidence: 99%
“…These can include: developing personas, creating fictional characters to understand and empathise with a particular audience Cooper (1999); Picking et al (2010); standards review, using a set of guidelines to ensure that constraints are accommodated within a design (e.g. Chisholm et al (2001)); automated checking, using tools which evaluate designs against set guidelines automatically Abascal et al (2004); Kasday (2000); and user testing, typically involving both, experts conducting a heuristic analysis to identify problems in a design Nielsen and Molich (1990), and, potential end-users providing general feedback on the use of a prototype Rubin and Chisnell (2008).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to evaluate the accessibility of webpages, it should be checked whether the pages include layout-purpose <table> tags. Several methods and tools have been proposed and developed for web accessibility (Cooper, 1999;Scapin et al, 2000;Ivory, 2003;Ivory et al, 2003;Abascal et al, 2004;Brajnik, 2004;Beirekdar et al, 2005;. Accessibility tools are listed in (W3C, 2006;Perlman, 2008) and compared in (Brinck et al, 2002).…”
Section: Introductionmentioning
confidence: 99%